Which Socialism, Whose Détente? - Bracke, Maud (2007)
This study analyzes the impact of the Czechoslovak crisis of 1968–1969 on the two major communist parties in the West: the Italian and French ones. Discusses the central strategic and ideological tensions which these parties needed to deal with: domestic belonging versus allegiance to the world communist movement, doctrinal orthodoxy in a context of rapid societal changes, and the question of revolution and reform. These key problems were situated in different contexts: the crisis in the “wor...